Kritik Ibn Jawzi terhadap Ulama dalam Kitab Talbis Iblis - Abbas, Rafid (ISLAMICA: Jurnal Studi Keislaman, 2009)
In this paper we are concerned with elaborating the critiques of Ibn Jawzi against the ulama of his time in his Talbis Iblis. By the ulama Ibn Jawzi means the learned in any field of knowledge such as QurâÃ¢nic reading (qiraâah), prophetic tradition (hadith), jurisprudence (fiqh), language, letter, and the art of speech (khitabah). We will analyze the motif behind Ibn Jawziâs warning to the ulama that they can âby virtue of their knowledge- be manipulated by the Satan. Not all knowledge is therefore good. Hence, we are interested in exposing the nature of knowledge in Ibn Jawziâs concept and what are the kinds of knowledge that may lead to Satanic manipulation. The paper will also discuss Ibn Jawziâs advice to the ulama so that they may not fall victim in the trap of the Satan.